Stain susceptibility of a giomer and a particulate-filled injectable composite with one-step and multi-step polishing techniques, and color recovery after brushing and repolishing - Eman Samy Ibrahim; Reham Mohamed Salem; Khaled Aly Nour (BMC Oral Health, 2026)
Abstract Objectives This study evaluated the stain susceptibility and color recovery of Giomer and highly filled injectable composite compared with a nano-filled packable composite, using one-step and multi-step polishing systems. Methods Ninety composite specimens were prepared from Filtek Z350, Beautifil Flow Plus, and G-ænial Injectable and divided into three polishing subgroups ( n = 10): Mylar strip, OneGloss, and Enamel Plus Shiny. After baseline color measurement (T 0 ), the specimens were immersed in coffee at 37 °C for 30 days. Color changes were measured using a Vita EasyshadeV spectrophotometer after brushing using a soft toothbrush (ΔE_brushing; T₁–T₀) and after repolishing using AL 2 0 3 paste (ΔE_repolishing; T₂–T₀). Data were analyzed using a linear mixed model with Yeo–Johnson transformation and Holm’s correction (α = 0.05). Results A significant interaction was observed among material type, polishing system, and color change ( p = 0.020). G-ænial Injectable showed the lowest stain susceptibility (ΔE_brushing = 2.84; ΔE_repolishing = 1.88). Multi-step polishing significantly improved stain resistance for all tested materials. Repolishing significantly reduced discoloration in all groups ( p < 0.001) by increasing L* values and reducing shifts in a* and b* coordinates. Among all materials, only the multi-step-polished G-ænial Injectable achieved color change values that approached the acceptability threshold (ΔE₀₀ ≤ 1.8). Conclusion Highly filled injectable composites and multi-step polishing improved stain resistance and color recovery of resin composites, whereas S-PRG fillers and matrix-set surfaces increased stain susceptibility. Clinical relevance Multi-step polishing enhances esthetics, while repolishing improves restoration longevity.